Lifting and exertion injuries decrease after implementation of an integrated hospital-wide safe patient handling and mobilisation programme. Issue 5 (25th October 2016) - Dennerlein, Jack T; O'Day, Elizabeth (Tucker); Mulloy, Deborah F; Somerville, Jackie; Stoddard, Anne M; Kenwood, Christopher; Teeple, Erin; Boden, Leslie I; Sorensen, Glorian; Hashimoto, Dean
Abstract : Objective: With increasing emphasis on early and frequent mobilisation of patients in acute care, safe patient handling and mobilisation practices need to be integrated into these quality initiatives. We completed a programme evaluation of a safe patient handling and mobilisation programme within the context of a hospital-wide patient care improvement initiative that utilised a systems approach and integrated safe patient equipment and practices into patient care plans. Methods: Baseline and 12-month follow-up surveys of 1832 direct patient care workers assessed work practices and self-reported pain while an integrated employee payroll and injury database provided recordable injury rates collected concurrently at 2 hospitals: the study hospital with the programme and a comparison hospital. Results: Safe and unsafe patient handling practice scales at the study hospital improved significantly (p<0.0001 and p=0.0031, respectively), with no differences observed at the comparison hospital. We observed significant decreases in recordable neck and shoulder (Relative Risk (RR)=0.68, 95% CI 0.46 to 1.00), lifting and exertion (RR=0.73, 95% CI 0.60 to 0.89) and pain and inflammation (RR=0.78, 95% CI 0.62 to 1.00) injury rates at the study hospital. Changes in rates at the comparison hospital were not statistically significant. Conclusions: Within the context of a patient mobilisation initiative, a safe patient handling and mobilisation programme was associated with improved work practices and a reduction in recordable worker injuries. This study demonstrates the potential impact of utilising a systems approach based on recommended best practices, including integration of these practices into the patient's plan for care.